Flower Bud Differentiation In Piper Sp. - Rajan PS (Department of Plantation Crops and Spices, College of Horticulture, 1985)
Studies were undertaken at the College of Horticulture, Vellanikkara during 1983-’84 in Panniyur-1 and Karimunda varieties of pepper to collect information on the factors influencing flower bud differentiation and on the histological aspects of the process. Among the climatic factors maximum and minimum temperature during the preceding summer as well as the monsoon showers exhibited significant positive correlation with flower bud differentiation process. Among the nutritional factors studied, carbohydrates and C/N ratio were found to be high prior to the peak differentiation period. However, these failed to show significant statistical correlation. Significant accumulation of nitrogen was found in the shoots prior to differentiation. Phosphorus and potassium contents were not correlated with the process. Inhibitor content of the shoots prior to differentiation was found to negatively influence the process. Peak period of differentiation was observed from the middle of June to the end of July in Panniyur-1, while it was a little advanced in Karimunda (from the beginning of June to the middle of July). There were no fundamental differences in the histological aspects of flower bud differentiation between the two varieties. The bud which was conical during the vegetative phase changed into a dome shaped structure during the transition. Afterwards, this grew into a cylindrical structure on the sides of which bract and flower primordial developed in aeropetal succession. Differentiation and development of ovary wall, integuments, ovules, pollen sacs, pollen grains etc. followed. The whole process of differentiation was completed within about 25 days of its commencement.